Spatio-Temporal Electron Propagation Dynamics in Au/Fe/MgO(001) in Nonequilibrium: Revealing Single Scattering Events and the Ballistic Limit - Markus Heckschen; Yasin Beyazit; Elaheh Shomali; Florian Kühne; Jesumony Jayabalan; Ping Zhou; Detlef Diesing; Markus E. Gruner; Rossitza Pentcheva; Axel Lorke; Björn Sothmann; Uwe Bovensiepen (PRX Energy, 2023)
Understanding the microscopic spatio-temporal dynamics of nonequilibrium charge carriers in heterosystems promises optimization of process and device design towards desired energy transfer. Hot electron transport is governed by scattering with other electrons, defects, and bosonic excitations. Analysis of the energy dependence of scattering pathways and identification of diffusive, superdiffusive, and ballistic transport regimes are current challenges. Beyond our previous studies on the Au/Fe(001) heterostructure, in this work, we determine the energy-dependent change of the electron propagation time through epitaxial Au/Fe(001) heterostructures as a function of Au layer thickness. We do so by employing femtosecond time-resolved two-photon photoelectron emission spectroscopy for energies of 0.5–2.0 eV above the Fermi energy. We describe the laser-induced nonequilibrium electron excitation and injection across the Fe/Au interface using real-time time-dependent density functional theory and analyze electron propagation through the Au layer by microscopic electron transport simulations. We identify ballistic transport of minority electrons at energies with a nascent optically excited electron population, which is determined by the combination of photon energy and the specific electronic structure of the material. At lower energy, superdiffusive transport with 1–4 scattering events dominates. The effective electron velocity accelerates from 0.3 to 1 nm/fs with an increase in the Au layer thickness from 10 to 100 nm. This phenomenon is explained by electron transport that becomes preferentially aligned with the interface normal for thicker Au layers, which facilitates electron momentum or energy selection by choice of the propagation layer thickness.